Athanasiou, Androulla - (:unkn) unknown (My University, 2026)
Dr. Androulla Athanasiou has been the Director of the Cyprus University of Technology (CUT) Language Centre (LC) since 01/01/2024. She has been an English Language Instructor at the Language Centre of the Cyprus University of Technology (CUT) since 2009. She holds an MA in English and Language Studies and Methods from Warwick University (2000), an MA in Educational Leadership from the European University Cyprus (2012) and a PhD in English Language Teaching from Warwick University (2005). During her teaching experience, she has engaged in course development and material design, both at an undergraduate and a postgraduate level. She has taught both in private and state Higher Education Institutions in Cyprus, as well as English for Academic Purposes at Warwick University. Apart from the ESAP courses, she also teaches an undergraduate course, ‘Issues in Bilingualism/Multilingualism’, to 4th year undergraduate students studying Speech and Language Therapy, as well as on the MA in CALL programme, offered by the CUT Language Centre in collaboration with the Department of Multimedia and Graphic Arts.
Keywords: The use of technology in language teaching/learning (Computer Assisted Language Learning); Learner Autonomy; Collaborative Learning; The use of Common European Framework of References for Languages (CEFR); Material Design